Frequent ventricular premature beats increase blood pressure variability in rats - MIAO Chao-yu; XU Li-ping; LIU Jian-guo; XIE He-hui; YUAN Wen-jun; SU Ding-feng (Acta Pharmacologica Sinica, 2016)
AIM: The present study was designed to test a hypothesis that nonfatal ventricular arrhythmia such as ventricular premature beats (VPB) is a contributing factor in the elevation of blood pressure variability (BPV). METHODS: Blood pressure (BP) and electrocardiogram were continuously recorded. The relation between VPB and BPV was observed under conscious state in chronic myocardial infarction (MI) rats one month after ligation of the left coronary artery, and further verified under anesthetized state in rat model of ventricular arrhythmia produced by acute intravenous infusion of aconitine. RESULTS: MI rats exhibited a big difference in the count and pattern of VPB, and were divided into no VPB, occasional VPB, and frequent VPB groups. Among the three groups, there were no differences in BP, heart period (HP), and MI size. However, BPV was markedly higher in frequent not occasional VPB rats, and HP variability (HPV) was larger in both frequent and occasional VPB rats, when compared with no VPB rats. In the whole population of MI rats, BPV was positively correlated with VPB and HPV, not with BP, HP and MI size. Infusion of aconitine had no effect on BP, HP, BPV, and HPV during the period without VPB. Frequent VPB after several minutes of aconitine infusion induced significant increase in BPV and HPV with no change in BP and HP. BPV was also positively correlated with VPB and HPV, not with BP and HP. Hemodynamics in aconitine-evoked ventricular tachycardia was characterized as lower BP, higher BPV, and higher HPV. CONCLUSION: High BPV can be caused by frequent not occasional VPB in rats.